EFFECTIVENESS OF SOCKET PRESERVATION IN MAINTAINING ALVEOLAR BONE VOLUME: A SYSTEMATIC REVIEW - Fahrur Rozi Lubis; Irma Ervina; Martina Amalia (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Alveolar bone undergoes dimensional changes due to resorption after tooth extraction, which can make it difficult to place a denture or implant. Preservation socket procedures are performed at the time of tooth extraction with the aim of minimizing alveolar bone resorption. The purpose of this systematic review is to analyze the effectiveness of socket preservation in preserving alveolar bone. Review: This systematic review was conducted through an electronic literature search in PubMed, Wiley, and Sciencedirect, which was used to obtain a number of Randomized Clinical Trial (RCT) articles on the effectiveness of socket preservation with graft material versus no socket preservation. This systematic review was conducted following the Preferred Reporting Items for Systematic reviews (PRISMA) guidelines. Based on the 417 articles screened, there were 24 duplicates, and after the articles were included by the criteria of: RCT, human study, publication in English, within the last five years and focusing on the methods and outcomes of socket preservation, 5 articles were found to be relevant. Conclusion: Of the five studies reviewed, one study using allograft material and four studies using xenograft material, the results were that socket preservation can reduce alveolar bone resorption and can maintain the horizontal and vertical dimensions of alveolar bone compared to no socket preservation